Public Awareness About Sepsis in Türkiye: A Survey Study - Kurum, Cüneyt; İşçanan, Ali and Alioğlu, Aslıhan and Karataş, Zeliha Sena and Alothman, Youssef and Ülker, Kerem and Dik, Şeyma Nur and Palabıyık, Abdullah and Aydın, Züleyha and Balkan, İlker İnanç (Cerrahpaşa Medical Journal, 2024)
Objective: Sepsis is a severe medical condition characterized by life-threatening organ dysfunction due to an imbalanced immune response to infection. Delayed diagnosis often leads to high mortality rates, with approximately 50 million cases and 11 million deaths globally each year. Despite its significant impact on health and economics, public awareness of sepsis is low, especially among non-healthcare professionals. This study, conducted by fifth-year students from İstanbul University-Cerrahpaşa, Cerrahpaşa Faculty of Medicine, aims to evaluate and enhance sepsis awareness among diverse segments of the Turkish population. Methods: Ethical approval was obtained from the İstanbul University-Cerrahpaşa Clinical Research Ethics Committee on April 5, 2024. Data collection involved a survey adapted from literature, administered face-to-face and through Google Survey Form over 1 month. The sample size was adjusted for Türkiye’s population, excluding physicians and those unable to respond independently. Data analysis utilized the Statistical Package for Social Sciences version 26.0 software (IBM Corp.; Armonk, NY, USA). Results: The study comprised 852 participants, predominantly female (53.4%), with an average age of 32; 49% were university-educated. Only 40.3% had prior knowledge of sepsis. Awareness was significantly higher among females (P < .001), peaking among 22-27 year-olds. Higher education and healthcare professions correlated with increased awareness (P < .001). Conclusions: The research highlights inadequate sepsis awareness in Türkiye, particularly among non-healthcare professionals. Despite awareness among university-educated individuals and healthcare workers, broader societal awareness remains deficient. Media coverage of sepsis fails to reflect its public health significance. Higher awareness among females suggests stronger health literacy. Further comprehensive research is crucial to address these findings effectively. Cite this article as: Kurum C, İşçanan A, Alioğlu A, et al. Public awareness about sepsis in Türkiye: a survey study. Cerrahpaşa Med J. 2024;48(3):279-283.